Wholeness and Holiness in Education: An Islamic Perspective by Zahra Al Zeera (UK: The International Institute of Islamic Thought, and Biddles Limited, 2001. 158 pages.) (American Journal of Islam and Society, 2003)
Wholeness and Holiness in Education: An Islamic Perspective is a veryinteresting book. Although the book is a result of her experience as aMuslim graduate student in Canada, she does not mention any personal reasonsfor writing this book, but rather tackles it very lightly without mentioningthe hard experiences she faced when her faith was questioned. AMuslim who has taken her faith for granted for years and had had little orno communication with the West was questioned for the first time in her lifeabout many aspects of her faith and found herself unable to provide adequateanswers. Her book is the result of such an experience, one whichmany others in her circumstances and situation have faced and will have toface. Although the author frequently tackles abstract ideas, she always providesscholarly explanations and discussions by quoting and elaboratingupon many well-known figures in various disciplines.The book is divided into four parts and has a total of nine chapters. Thefirst part, “Reflection on Personal Experience,” includes two chapters. Inthem, she tries to take the reader from her own personal experience to thebook’s goal: preparing Muslim students in their homelands’ educationalsystems to think and question their faith so that they can stand on solidground. In chapter 1, “The Spiritual and Intellectual Journey,” she apologizesfor including her personal experience growing up as a Muslim.Actually, more elaboration upon such experiences and on the conflicts shefaced while studying in Canada would have been appreciated, as such atopic requires that personal experiences be shared, given that they are notlimited to one person but rather to millions of individuals. Chapter 2,“Spirituality: Woman’s Best-Kept Secret,” further analyzes the significanceof such experiences to women specifically ...